Strategic Approach to Increase Purchase Interest in Alternative Energy Vehicles in Bogor - Susilo, Susilo; Muharam, Hari; Pranowo, Agus Setyo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research investigates the influence of product quality, social media marketing, and price perception on consumers' intention to purchase electric vehicles, with brand awareness serving as a mediating factor. Conducted in Bogor City, the study employed a quantitative method involving 385 respondents selected through purposive sampling. Data analysis was performed using SEM-LISREL 8.80. The findings reveal that product quality has a significant impact on both brand awareness (t = 3.48) and purchase intention (t = 3.61). Social media marketing also significantly influences brand awareness (t = 2.02) and purchase intention (t = 4.24), while price perception affects brand awareness (t = 2.36) and purchase intention (t = 3.44). Furthermore, brand awareness mediates the relationship between these variables and purchase intention (t = 4.20). The findings indicate that social media marketing is the most dominant factor affecting purchase intention, highlighting the importance of developing intensive and interactive digital marketing strategies. Practically, companies should focus on enhancing brand awareness and building positive consumer perceptions through social media, supported by high-quality products and competitive pricing, to accelerate electric vehicle adoption in Bogor.